Brain death diagnosis in adult for potential cadaveric organ donation in Bangladesh - Ahmed, Fatema; Ahsan, ASM Areef; Faruq, Mohammad Omar; Fatema, Kaniz; Saha, Debasish Kumar; Saha, Madhurima; Nazneen, Suraiya; Zaman, Md Shah; Karim, Md Rezaul; Alam, Khan Md Shafikul; et al. (Bangladesh Critical Care Journal, 2017)
Aim: The objectives of this study was (i) To increase knowledge of the epidemiological and clinical features of patients diagnosed with brain death for potential cadaveric organ donation (ii) To determine the compliance of guidelines brain death based on neurological criteria (iii) To analyse process of clinical decision making regarding continuation of life support after brain death diagnosis. Materials and Method: A prospective observational study was carried out in a 12 bed adult ICU of a tertiary care hospital with neurosurgery services in Bangladesh over a period of 2 years from January 2015 to December2016. All patients admitted during this period were scrutinized for identification of brain death and impending brain death. They were analyzed for causes of brain death, diagnosis of brain death, and the use of ancillary testing. Potential for organ donation was also kept in mind. Results: During the study period, total 1387 patients were admitted into the study ICU and there were 329 deaths. And out of them 69 were diagnosed as brain death. The main causes of brain death were intracerebral haemorrhage (32/69, 46%), followed by ischemic stroke (11/69, 16%), subarachnoid haemorrhage (11/69, 12%), traumatic brain injury (8/69, 12%) and brain tumor and CNS infection. The diagnosis of brain death was made in 33 (47%) cases in the first 48 hours and 23 (33%) cases in 48-96 hours of ICU admission. With the exception of two cases, all study patients had GCS score ? 8 (97%). Brain death was diagnosed according to American Academy of Neurology (AAN) 2010 guidelines. Only two cases Electroencephalography was done for family request. All life-sustaining measures were withdrawn in 67 (97%) cases with consent of family. Conclusion: There is no scarcity of brain death cases in our country according to our study. We need to promote and popularize the cadaveric organ transplant along with living donor transplantation. Bangladesh Crit Care J March 2017; 5(1): 48-52